The Iron Cage of Development: A Cross‐National Analysis of Incarceration, 2000 – 2015. Issue 2 (20th January 2021) - Clark, Rob; Herbolsheimer, Chancey
Abstract : Comparative studies on incarceration rely heavily on demand‐based explanations, suggesting that prison rates are driven by sentencing practices and the criminalization of certain activities. In turn, such theories are often tested against the backdrop of factors that regulate the supply of offenders and facilities. We agree that supply and demand factors may be proximate causes of prison population sizes, but that socio‐economic development is central to shaping the larger narrative. In this study, we identify a "criminological Kuznets curve, " whereby the association between incarceration rates and economic development is curvilinear, reaching its peak among middle‐income countries. Drawing from a sample of 680 observations across 111 countries during the 2000 – 2015 period, we find that incarceration is strongly associated with factors rooted in development, including crime rates, the age structure of the population, and democratization. We find that human rights conditions are positively associated with incarceration, which we interpret as a shift away from more severe forms of punishment (e.g., death penalty, torture) as societies modernize. Meanwhile, the effects of several other predictors (government expenditures and income inequality) are conditioned by a country's level of development. Finally, when adding country fixed effects, we show that economic growth increases prison rates among low‐income countries, but reduces them among affluent nations, which directly contributes to the criminological Kuznets curve. Overall, we conclude that prison populations are shaped by both supply and demand factors, but that development processes help organize these relationships.